2017
DOI: 10.5551/jat.36004
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Management in a Japanese Community:Attainment Rate of Target Set by the Japan Atherosclerosis Society Guidelines for the Prevention of Atherosclerotic Cardiovascular Diseases 2012

Abstract: Aim: The Japan Atherosclerosis Society (JAS) guidelines for the prevention of atherosclerotic diseases 2012 (JAS2012) proposed lipid management targets; however, less data is available regarding the attainment rates of each target in community-based settings. Therefore, we assessed the attainment rates of lipid management targets among subjects who underwent Japanese specific health checkups.Methods: A total of 85,716 subjects (male = 29,282, 34.2%) aged 40–74 years who underwent specific health checkups from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Promotion and preventive measures to manage cardiovascular disease risk factors in community level, specifically in renal dysfunction patients, is of no less importance. A recent study investigating lipid management targets in Japan showed inadequate attainment rates in the population, raising alarm for its improvement 43 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promotion and preventive measures to manage cardiovascular disease risk factors in community level, specifically in renal dysfunction patients, is of no less importance. A recent study investigating lipid management targets in Japan showed inadequate attainment rates in the population, raising alarm for its improvement 43 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Serum creatinine was only measured on admission and in individual centers, thereby influencing its accuracy. Furthermore, admission NIHSS, a strong predictor of stroke outcome 43 ) , was not incorporated due to its high rate of missing data. However, we perceive this issue to be overcome by using JCS, a Japanese-based consciousness level score developed in the same year as the Glasgow Coma Scale, which has been proven to have good predictability of stroke outcome 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…83) . Insight may be gained from country-specific studies, for example a Japanese single-centred observational study demonstrated remarkably low periprocedural stroke rates (0.68%) and annual stroke rates (0.64%) for CEA in asymptomatic patients.…”
Section: Asymptomatic Carotid Stenosismentioning
confidence: 99%
“…Tests were also performed to clarify whether the coefficients differed between the employed and the others. 36,[41][42][43][44] . Employed people in a company, particularly in large-scale companies, have more opportunities to undergo medical health check-ups and obtain health information than the others 45) .…”
Section: Discussionmentioning
confidence: 99%